2019
DOI: 10.1186/s12872-019-1166-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the autonomic nervous system by analysis of heart rate variability in the preterm infants

Abstract: Background Premature infants may present with damage to the autonomic nervous system (ANS), which may be related to poorer neurological development. Among the techniques used to evaluate the ANS, heart rate variability (HRV) emerged as a simple, non-invasive, and easy to apply tool. The aim of the present study was to analyze and compare HRV in preterm infants at different times of hospitalization in order to verify the possible environmental relationships or clinical evolution with HRV. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 29 publications
0
20
0
1
Order By: Relevance
“…These results are not simply in line with a decrease of by Hoyer et al ( 2013 ), but they are also supported by other clinical findings. Namely, an increase of the short-term variability of the tachogram was found during the first days of life (De Souza Filho et al, 2019 ) and the absolute LF power can discriminate preterm and full-term infants with 84% accuracy (Mulkey et al, 2018 ). However, the highest performances in the PB and BB schemes are achieved when the fractal and spectral features are combined, as highlighted in bold in Table 4 and suggested by the concomitant increase of entropy and short-term variability of HRV found by De Souza Filho et al ( 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are not simply in line with a decrease of by Hoyer et al ( 2013 ), but they are also supported by other clinical findings. Namely, an increase of the short-term variability of the tachogram was found during the first days of life (De Souza Filho et al, 2019 ) and the absolute LF power can discriminate preterm and full-term infants with 84% accuracy (Mulkey et al, 2018 ). However, the highest performances in the PB and BB schemes are achieved when the fractal and spectral features are combined, as highlighted in bold in Table 4 and suggested by the concomitant increase of entropy and short-term variability of HRV found by De Souza Filho et al ( 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Namely, an increase of the short-term variability of the tachogram was found during the first days of life (De Souza Filho et al, 2019 ) and the absolute LF power can discriminate preterm and full-term infants with 84% accuracy (Mulkey et al, 2018 ). However, the highest performances in the PB and BB schemes are achieved when the fractal and spectral features are combined, as highlighted in bold in Table 4 and suggested by the concomitant increase of entropy and short-term variability of HRV found by De Souza Filho et al ( 2019 ). Interestingly, the highest performances are also achieved when the between bradycardias epochs are considered ( MAE = 1.56 weeks), which further reveals a bias effect of bradycardias in the description of autonomic maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed the usefulness of non-linear metrics over linear ones in evaluating the autonomic development (Uhrikova et al, 2015;de Souza Filho et al, 2019;Oliveira et al, 2019b), the interactions between ANS, brain, and stress axis (Thayer and Lane, 2000), and the infant's adaptation capacity (Gonçalves et al, 2017;Shaffer and Ginsberg, 2017;Urfer-Maurer et al, 2018).…”
Section: Metricmentioning
confidence: 99%
“…Autonomic modulation, estimated by heart rate variability (HRV) and regulated by sympathetic and parasympathetic pathways, has been increasingly used as a measure of term and preterm newborn stress and well-being [ 1 3 ].…”
Section: Introductionmentioning
confidence: 99%